Pescando memórias na praia do Paquetá - Christmann, Juliana Pugliese (2015)
This research is focused on the fishermen of Praia do Paquetá and their activities developed in this village, based on their memories. For this purpose, it was sought: to ascertain who are the fishermen of Praia do Paquetá, their origin, age composition, gender and activities that they develop in the community; to analyze participatory processes and community organizations to which they belong. This paper fits into the Research Line of Memory, Culture and Identity, having as benchmarks the assumptions about social memory, governance and social mobilization. The research is of qualitative nature and the methodological approach was based on the methodology of oral history. It was conducted thematic interviews with 12 fishermen and the data were analyzed and interpreted following the content analysis technique, in the thematic modality. As results, it points to the formation of links between fishermen and the river, as well as its perspective on the past, present and the future of the village. This portrait of yesterday and today of the fishermen and the village is recorded in the book "Fishing Memories in Praia do Paquetá", the final product of this work.